2008
DOI: 10.1370/afm.867
|View full text |Cite
|
Sign up to set email alerts
|

Using Multiple Sources of Knowledge to Reach Clinical Understanding of Chronic Fatigue Syndrome

Abstract: PURPOSE Chronic fatigue syndrome (CFS), or myalgic encephalitis (ME), is a contentious condition and often a diagnosis of exclusion. Current policy in the United Kingdom recommends management in primary care. We explored how patients with CFS/ME and family physicians understand this condition and how their understanding might affect the primary care consultation. METHODSWe undertook a qualitative study with patients and family physicians from North West England participating in a primary care-based randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 41 publications
(50 reference statements)
4
60
0
Order By: Relevance
“…For doctors who are trained to work on the basis of evidence-based biomedical knowledge and technological proof, somatic symptoms unsubstantiated by observable biomarkers to verify organic disease are challenging. When their ability to identify, explain and treat patients’ ailments is constrained by an uncertain biomedical foundation, they often feel powerless, inadequate, dissatisfied, frustrated and anxious (Åsbring & Närvänen, 2003; Chew-Graham, Cahill, Dowrick, Wearden, & Peters, 2008; Chew-Graham, Dowrick, Wearden, Richardson, & Peters, 2010; Howman, Walters, Rosenthal, Ajjawi, & Buszewicz, 2016; Libert et al, 2016; Murray, Toussaint, Althaus, & Löwe, 2016). For patients, experiences of uncertainty can increase psychological distress, intensify sensitivity to pain (Rosendal et al, 2013; Taylor, Marshall, Mann, & Goldberg, 2012; Weiland et al, 2012; Wright, Afari, & Zautra, 2009), and result in poorer health (Neville, 2003), reduced quality of life and diminished confidence (Ogden et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For doctors who are trained to work on the basis of evidence-based biomedical knowledge and technological proof, somatic symptoms unsubstantiated by observable biomarkers to verify organic disease are challenging. When their ability to identify, explain and treat patients’ ailments is constrained by an uncertain biomedical foundation, they often feel powerless, inadequate, dissatisfied, frustrated and anxious (Åsbring & Närvänen, 2003; Chew-Graham, Cahill, Dowrick, Wearden, & Peters, 2008; Chew-Graham, Dowrick, Wearden, Richardson, & Peters, 2010; Howman, Walters, Rosenthal, Ajjawi, & Buszewicz, 2016; Libert et al, 2016; Murray, Toussaint, Althaus, & Löwe, 2016). For patients, experiences of uncertainty can increase psychological distress, intensify sensitivity to pain (Rosendal et al, 2013; Taylor, Marshall, Mann, & Goldberg, 2012; Weiland et al, 2012; Wright, Afari, & Zautra, 2009), and result in poorer health (Neville, 2003), reduced quality of life and diminished confidence (Ogden et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Factors that influence how trusted GPs are include feeling one's individual experience has been understood and the perceived thoroughness of the evaluation. 27 This is likely to be particularly important in MUS where individuals recognise that their condition is at the limits of medical knowledge 28 , describe the effort involved in presenting as credible and legitimate 29 and believe they are taken less seriously than their counterparts with explained symptoms. 30 Elsewhere, it has been shown that in order for patients to feel able to disclose psychological problems, GPs must first provide a safe place in which they feel listened to and understood.…”
Section: Discussionmentioning
confidence: 99%
“…In cases where the physical pathology is absent, patients may feel as though their complaints are not a legitimate use of consultation time [45,46]. In response to this need to appear credible [47], patients may use graphic and emotional language [38] in an attempt to convince the PCP of the seriousness of their complaints [41,43,48].…”
Section: Communication and Consultation Behaviourmentioning
confidence: 99%